Driving HIV-1 into a Vulnerable Corner by Taking Advantage of Viral Adaptation and Evolution - Harada, Shigeyoshi; Yoshimura, Kazuhisa (Frontiers in Microbiology, 2017)
Introduction Human immunodeficiency virus type-1 (HIV-1) is responsible for the AIDS pandemic. HIV-1 exhibits extremely high levels of genetic diversity (Rambaut et al., 2004) indicating that rapidly changing genetic variation can confer on the virus the capacity to escape the immune system and anti-retroviral therapy (ART). The HIV-1 components presenting the highest degree of sequence diversity are the surface-expressed viral envelope glycoproteins (Env), which are prime targets for both entry inhibitors and neutralizing antibodies (NAbs) (Goulder and Watkins,2008). The function of Env is to facilitate the entry of HIV-1 into the target cell, a process mediated by recognition of the CD4 receptor and coreceptor (usually CCR5 or CXCR4) on the cellular membrane (Dalgleish et al.,1984;Klatzmann et al.,1984;Choe et al.,1996;Deng et al.,1996;Doranz et al.,1996;Dragic et al.,1996;Feng et al.,1996). Env is composed of the surface glycoprotein, gp120, and the transmembrane glycoprotein, gp41, which associate as a non-covalent complex to form a single subunit of a trimeric viral envelope spike (Wyatt and Sodroski, 1998). Gp120 is responsible for binding to CD4 and the coreceptor, whereas gp41 anchors the Env machinery at the viral membrane and induces membrane fusion during viral entry (Freed and Martin,1995;Bazan et al.,1998). Inhibitors that block either the interaction of Env with the CD4 receptor, the coreceptor, or the fusion reaction have been identified. Currently, two entry inhibitors have been licensed for clinical use, the fusion inhibitor, enfuvirtide (T-20) (Robertson,2003), and the CCR5 inhibitor, maraviroc (MVC) (Dorr et al.,2005;Gulick et al.,2008). As with any anti-retroviral drug, HIV can develop resistance to enfuvirtide and MVC. The main mechanism of resistance to enfuvirtide is the selection of changes in a 10 amino acid motif between residues 36 and 45 in the HR1 region of gp41 that forms part of the binding site of enfuvirtide (Greenberg and Cammack,2004). On the other hand, clinical resistance to MVC involves different genetic alterations in env giving rise to highly divergent Env phenotypes (Roche et al.,2013). Potential molecular mechanisms of resistance to MVC include tropism switching to CXCR4-using (X4) viruses (Westby et al.,2006;Raymond et al.,2015), increased kinetics of the entry step (Reeves et al., 2002; Putcharoen et